2023
DOI: 10.1002/smll.202309264
|View full text |Cite
|
Sign up to set email alerts
|

Domain‐Limited Sub‐Nanometer Co Nanoclusters in Defective Nitrogen Doped Carbon Structures for Non‐Invasive Drug Monitoring

Zhichao Yu,
Juan Tang,
Yuan Gao
et al.

Abstract: In this work, sub‐nanometer Co clusters anchored on porous nitrogen‐doped carbon (C─N─Co NCs) are successfully prepared by high‐temperature annealing and pre‐fabricated template strategies for non‐invasive sensing of clozapine (CLZ) as an efficient substrate adsorption and electrocatalyst. The introduction of Co sub‐nanoclusters (Co NCs) provides enhanced electrochemical performance and better substrate adsorption potential compared to porous and nitrogen‐doped carbon structures. Combined with ab initio calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“… As for the NDAA/BiOI survey spectrum, the N element alongside Bi, I, and O was also observed. The characterized peaks of N 1 s at 405.8 and 400.1 eV in Figure f can be attributed to –NO 2 and N-(C) 3 , aligning with the NDAA molecular structure. Additionally, the Bi atom content dropped, while the corresponding C and N contents increased when compared to BiOI (Table S1), confirming its successful integration onto the surface of BiOI.…”
Section: Resultsmentioning
confidence: 99%
“… As for the NDAA/BiOI survey spectrum, the N element alongside Bi, I, and O was also observed. The characterized peaks of N 1 s at 405.8 and 400.1 eV in Figure f can be attributed to –NO 2 and N-(C) 3 , aligning with the NDAA molecular structure. Additionally, the Bi atom content dropped, while the corresponding C and N contents increased when compared to BiOI (Table S1), confirming its successful integration onto the surface of BiOI.…”
Section: Resultsmentioning
confidence: 99%
“…The results demonstrated that there was no significant disparity in the recovery of saliva samples from the three volunteers before and after food intake for the DA test using both methods (Figures S7 and S8). , The developed sensor showcased the potential for further advancements in nanoengineering and biomedicine by efficiently and sensitively detecting fluctuations in salivary DA levels.…”
Section: Resultsmentioning
confidence: 99%
“…The split peaks of N (1s) indicated four N environments, i.e., pyridinic N (397.8 eV, 36.76 at%), pyrrolic N (398.9 eV, 3.27 at%), graphitic N (400.1 eV, 52.53 at%) and oxidized N (402.4 eV, 7.44 at%). Furthermore, the O(1s) split peaks at 531.7 and 536.3 eV were assigned to CO and C–OH, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%